Fully robotic Ivor–Lewis esophagectomy (RAMIE4) for esophageal cancer after emergency surgery and ligation of the gastroduodenal artery. Issue 2 (February 2019) - Mann, Carolina; Hadzijusufovic, Edin; Lang, Hauke; Grimminger, Peter P.
We report a case of a 69-year-old patient with esophageal cancer and severe upper gastrointestinal bleeding during neoadjuvant radiochemotherapy who required mass transfusion followed by complex emergency procedures. Despite endoscopic stenting, the bleeding recurred, and thus emergency open surgery was required. Gastric wedge resection of the minor curvature necessitated by perforation caused by the endoscopic stent maneuver and duodenotomy with ligation of the gastroduodenal artery, as the cause of persistent intraluminal bleeding, were performed. The already prepared gastric conduit during the emergency operation did not become ischemic, even though the gastroduodenal artery, left gastric artery, and short gastric arteries were ligated during emergency surgery. After 2 months of recovery, a computed tomographic scan showed collateral perfusion of the conduit via the superior mesenteric artery. Therefore, a fully robotic (abdominal and thoracic) esophagectomy with pull-up of the gastric conduit was performed, with no post-surgical complications. The patient was discharged 10 days after the robotic esophagectomy. Six months after esophagectomy, the patient is in a good condition.